Ontogenetic development of attack behaviour by turbot larvae when exposed to copepod prey. (19th February 2018) - Højgaard, Jacob K; Bruno, Eleonora; Støttrup, Josianne G; Hansen, Benni W
Abstract: Identification of fish larval behavioural traits permitting capture of specific live prey sizes is an important part of optimizing production of marine larvae. We investigated the capture success of turbot larvae (S cophthalmus maximus ) at two development stages, 8 and 10 days post‐hatch (DPH), when offered small nauplii (129–202 μm), large nauplii (222–278 μm) and copepodites (342–542 μm), of the calanoid copepod Acartia tonsa . At 8 DPH, turbot larvae had the highest capture success (67%) when offered small nauplii, with a lower capture success of large nauplii (27%) but totally lacked the capabilities to capture copepodites. At DPH 10, the larvae increased the capture success of large nauplii (47%) and achieved a few successful attacks on copepodites. Energetically, large nauplii were the most beneficial at both larval development stages. The swimming kinematics of the period prior to a strike by the larva on the copepod was examined, and the approach pattern of the larva was identified as a controlling mechanism for their strike distance, with the initial approach speed of larva at DPH 10 being significantly less than at DPH 8. In all successful attacks, the strike distance was less than 1.17 mm and was significantly lower than unsuccessful attacks. Since the approach pattern of the larva is linked to its capture success, it could be used as the basis for a feeding scheme based on the swimming performance of individual batches of turbot larvae.